Successful treatment with ABL tyrosine kinase inhibitor for patients with acute myeloid leukemia with BCR-ABL1. (2021) - Takeuchi, Asako; Kondo, Toshinori; Tasaka, Taizo; Yamada, Seiko; Hirose, Tadashi; Fukuda, Hirofumi; Shimizu, Risa; Matsuhashi, Yoshiko; Kondo, Eisei; Wada, Hideho
Abstract: Acute myeloid leukemia (AML) with BCR-ABL1 is rare and has a poor prognosis with conventional chemotherapy or ABL tyrosine kinase inhibitors (TKIs) alone. We reported a case of AML with BCR-ABL1 patient who was successfully treated with dasatinib alone; additionally, we previously reported another case of long-term remission maintained with imatinib monotherapy. These results suggested that a treatment with a novel and significantly potent TKI may be effective in AML with BCR-ABL1 patients with low tumor burden and without additional chromosome aberrations and ABL kinase domain mutations.